Help, harm or hinder? Non-governmental service providers' perspectives on families and gender-based violence against women with intellectual disabilities in South Africa. Issue 1 (2nd January 2017) - Meer, Talia; Combrinck, Helene
Abstract: Through in-depth interviews with service providers from non-governmental organisations ( n = 58), this article describes the intricacy of familial relationships for women with intellectual disabilities in South Africa who experience gender-based violence. The findings suggest that families navigate social stigma, limited resources and isolation, whilst trying to be vigilant against gender-based violence and disability-related violence, and respond to it as it happens. However, family members are also simultaneously implicated in violence perpetration. We suggest that a social relational model of disability could help account for these crucial intra-familial dynamics.